2007
DOI: 10.1111/j.1551-2916.2007.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical Synthesis of a High‐Aspect‐Ratio Platelet NaNbO3 Template

Abstract: A high‐aspect‐ratio platelet sodium niobate (NaNbO3) was synthesized by a topochemical reaction. Plate‐like layered‐perovskite Bi2.5Na3.5Nb5O18 (BNN5) as a precursor was first prepared, and then Bi3+ in the precursor phase was replaced by Na+ through topotactic conversion and perovskite NaNbO3 formed at 950°C in NaCl molten salt. NaNbO3 crystals had an average length of 15 μm and a thickness of 0.5 μm. Scanning electron microscope and high‐resolution transmission electron microscope analyses indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…The overall molten slat synthesis [12][13] can be viewed as three sequential process: 1) the reactant dissolution; 2) the reactant transport through the melt; 3) the deposition of product onto its existent crystals. In the second MSS course, the BiNNx particles act as insoluble sites for the growth of NaNbO 3 particles.…”
Section: The Mechanism Of Platelet-like Nanbo 3 Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall molten slat synthesis [12][13] can be viewed as three sequential process: 1) the reactant dissolution; 2) the reactant transport through the melt; 3) the deposition of product onto its existent crystals. In the second MSS course, the BiNNx particles act as insoluble sites for the growth of NaNbO 3 particles.…”
Section: The Mechanism Of Platelet-like Nanbo 3 Particlesmentioning
confidence: 99%
“…In order to prepare textured lead free ceramics of alkali niobates via TGG or RTGG method, appropriate template particles with {0 0 l} crystal planes orientation need to be synthesized. It is reported that platelet perovskite ceramics particles can be synthesized by molten method [11][12][13]. Single-crystal NaNbO 3 particles with {100} facets have been synthesized from BiNN5 by two step molten salt method (or Topochemical synthesis method) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is crucial synthesizing high aspect ratio template for fabricating textured ceramics. Regarding the synthesis of platelike NaNbO 3 template particles, Saito et al proposed a new technique using topochemical microcrystal conversion (TMC) method [11,12]. This method preserves the morphology of precursor particles (platelike layered-perovskite Bi 2.5 Na 3.5 Nb 5 O 18 (BNN5) particles) and obtains objective compound particles (platelike NaNbO 3 particles), while the chemical composition of the particle is varied by ion exchange and intercalation reactions during TMC process.…”
Section: Introductionmentioning
confidence: 98%
“…Saito and Takao successfully synthesized micrometer sized plate-like KNbO 3 from layer-structured K 4 Nb 6 O 17 precursor. Yan et al also synthesized micrometer sized NaNbO 3 from layer-structured Bi 2.5 Na 3.5 Nb 5 O 18 as precursor [6][7][8][9][10]. The synthesis of micronsized KNbO 3 and NaNbO 3 is both via topochemical microcrystal conversion method.…”
Section: Introductionmentioning
confidence: 98%